1984
DOI: 10.1135/cccc19841061
|View full text |Cite
|
Sign up to set email alerts
|

The metachor as a characteristic of the association of electrolytes in aqueous solutions

Abstract: Based on the earlier paper introducing a concept of the apparent parachor of a solute in the solution, we have eliminated in the present work algebraically the effect which is introduced into this quantity by the additivity of the apparent molal volumes. The difference remaining from the apparent parachor after substracting the contribution corresponding to the apparent volume ( for which the present authors suggest the name metachor) was evaluated from the experimental values of the surface tension of aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Values of dγ lv /d m reported in the literature show significant variation, reflecting inconsistencies between different data sets. In the present work, using a consistent set of literature data, we obtained dγ lv /d m = 1.66 ± 0.02 mJ kg m –2 mol –1 . Moreover, it was found that the temperature dependence of γ lv is fully accounted for by the temperature dependence of γ lv,w .…”
Section: Calculationssupporting
confidence: 79%
“…Values of dγ lv /d m reported in the literature show significant variation, reflecting inconsistencies between different data sets. In the present work, using a consistent set of literature data, we obtained dγ lv /d m = 1.66 ± 0.02 mJ kg m –2 mol –1 . Moreover, it was found that the temperature dependence of γ lv is fully accounted for by the temperature dependence of γ lv,w .…”
Section: Calculationssupporting
confidence: 79%
“…For this study, surface tensions of water, aqueous electrolyte solutions, and molten salts were obtained from the primary literature, ,,, and from compilations of surface tension data. ,,− We focus on those inorganic salts and acids that are important in atmospheric aerosol systems. The work of Janz, in which surface tensions are given only as fitted equations (linear in temperature), is our primary source of information for molten salts.…”
Section: Surface Tensionmentioning
confidence: 99%
“…Liquid phase fluxes are always from the cold to the hot side and 18 S. OL1VELLA ET AL. Celeda and Skramovsky (1984). 9 Internal energy of the gas phase (J/kg):…”
mentioning
confidence: 99%